Parada cardiorrespiratória na unidade de terapia intensiva: análise das ocorrências iatrogênicas durante o atendimento Cardiopulmonary resuscitation in the intensive care unit: analysis of iatrogenic occurrences during attendance - Sandra Cristine da Silva; Katia Grillo Padilha (SciELO, 2000)
Trata-se de um estudo exploratório-descritivo que utilizou a Técnica do Incidente Crítico para obtenção e análise dos dados. Foram entrevistados 103 profissionais de enfermagem de duas UTIs gerais de um hospital do Estado de São Paulo, os quais forneceram relatos de situações de PCR . Do total de 126 situações obtiveram-se: falha na realização de procedimento técnico (58,6%); problemas relacionados a recursos materiais e equipamentos (31,2%) e falta de coordenação das atividades (8,6%). Quanto as conseqüências encontrou-se o óbito (70%) e a sobrevida imediata (30%) dos pacientes. Os resultados apontam a necessidade de investimentos na capacitação dos profissionais da UTI, bem como a importância do provimento adequado de materiais e equipamentos, com vistas a minimizar as ocorrências iatrogênicas no decorrer do atendimento. It is a descriptive-exploratory study which made use of the Critical incident Technique either to obtain and carry out the data analysis. Hundred and three nursing professionals working in two general ICUs of a Hospital located in the State of São Paulo, Brazil, provided reports concerning CPR situations. From the total of 126 situations obtained: failure in performing technical procedures (58,6%); problems concerning material resources and equipment (31,2%) and lacking coordination of activities (8,6%). Regarding the consequences generated by the type of attendance, patients¢ death (70%) and immediate survival (30%). The results point the need for higher investments in the multiprofessional ICU team capability, as well as in the need to furnish them with adequate material and equipment viewing to minimize iatrogenic occurrences during the attendance.